(untitled) (Nordic Journal of African Studies, 2001)
This paper explores the origin, growth and demise of autocracy in post-independence Zambia from a macro-historical perspective. It is argued that the underlying dynamic, which gradually turned Zambia into a virtual autocracy after its independence in 1964, stems from its colonial past, although augmented by the Zambians themselves. It is shown how emerging hero-worship within the dominant United National Independence Party (UNIP) turned the country’s first president, with the support of the people, into an autocrat. In the 1980’s the autocracy started to seriously crumble in the face of food riots and rising unemployment resulting from a deepening economic depression. It is concluded that, despite the return to a multi-party state in 1991, there are strong indications that this newly found democracy is already being undermined by the same dynamic that led to autocracy in the first place. [Ed.]